2022
DOI: 10.21037/jtd-22-599
|View full text |Cite
|
Sign up to set email alerts
|

Regional anesthesia for thoracic surgery: a narrative review of indications and clinical considerations

Abstract: Background and Objective: Surgical procedures involving incisions of the chest wall regularly pose challenges for intra-and postoperative analgesia. For many decades, opioids have been widely administered to target both, acute and subsequent chronic incisional pain. Opioids are potent and highly addictive drugs that can provide sufficient pain relief, but simultaneously cause unwanted effects ranging from nausea, vomiting and constipation to respiratory depression, sedation and even death. Multimodal analgesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 84 publications
0
3
0
2
Order By: Relevance
“…Given the high prevalence of opioids, their systemic administration is inevitable. One method is to combine regional or epidural anesthesia to reduce the use of systemic opioids [20]. Another approach to minimize adverse effects is to co-administer a peripheral opioid inhibitor such as naloxone, countering the effects of both exogenous and endogenous opioids [21].…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of opioids, their systemic administration is inevitable. One method is to combine regional or epidural anesthesia to reduce the use of systemic opioids [20]. Another approach to minimize adverse effects is to co-administer a peripheral opioid inhibitor such as naloxone, countering the effects of both exogenous and endogenous opioids [21].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have shown that SAPB can lead to slightly improved pain scores and reduced opioid consumption compared to no block or sham block [16]. Additionally, SAPB has shown hemodynamic stability during surgery, making it advantageous over PVB or thoracic epidural block [17]. However, it appears to be inferior compared to PVB or ESPB in terms of hospital LOS [6].…”
Section: Regional Analgesic Strategiesmentioning
confidence: 99%
“…Оскільки основною метою післяопераційного періоду є швидке одужання пацієнта, важливо забезпечити адекватне знеболювання, збереження свідомості та мобілізацію пацієнтів у ранній післяопераційний період. Цього можна досягти за допомогою мультимодального підходу до лікування хворого [25]. Пошук альтернативних методів пояснюється наявністю побічних ефектів та ускладнень методів знеболювання.…”
Section: обговоренняunclassified